Portable environmental monitoring system - Ehsan, M. Samiul; Biswas, Shukla; Nawar, Anika; Siddiqua, Rumali (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.